2019
DOI: 10.1002/smll.201805440
|View full text |Cite
|
Sign up to set email alerts
|

A Mussel‐Inspired Persistent ROS‐Scavenging, Electroactive, and Osteoinductive Scaffold Based on Electrochemical‐Driven In Situ Nanoassembly

Abstract: Conductive polymers are promising for bone regeneration because they can regulate cell behavior through electrical stimulation; moreover, they are antioxidative agents that can be used to protect cells and tissues from damage originating from reactive oxygen species (ROS). However, conductive polymers lack affinity to cells and osteoinductivity, which limits their application in tissue engineering. Herein, an electroactive, cell affinitive, persistent ROS‐scavenging, and osteoinductive porous Ti scaffold is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 61 publications
2
94
0
Order By: Relevance
“…Doping with nanophase polydopamine (PDA NPs) is a potential means to compensate for the defects of XK gels. Mussel-type PDA NPs prepared through the oxidative polymerization of dopamine have excellent properties for applications in the biomedicine [ 20 , 21 ]. The structure of PDA NPs is like that of natural melanin, and its advantages include strong light absorption capacity, good biocompatibility, and a simple preparation method [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Doping with nanophase polydopamine (PDA NPs) is a potential means to compensate for the defects of XK gels. Mussel-type PDA NPs prepared through the oxidative polymerization of dopamine have excellent properties for applications in the biomedicine [ 20 , 21 ]. The structure of PDA NPs is like that of natural melanin, and its advantages include strong light absorption capacity, good biocompatibility, and a simple preparation method [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…PDA has excellent biocompatibility and bioactivity. It has been confirmed that PDA can promote osteoblast cell adhesion and biomineralization [14]. We speculated that this nano-structured PPy/PDA NWs might have excellent promoting effect on osteogenesis than pure PDA and PPy.…”
Section: Characterization Of Ppy/pda Nwsmentioning
confidence: 75%
“…Actually, many studies confirmed that the PPy applied with electrical stimulation (ES) could promote the expression of proliferation and differentiation for tissue regeneration such as bone and nerves [11][12][13]. However, PPy does not display functional groups to help it adhere to surfaces [14]; therefore, generating composite materials with PPy and other adhesive polymers can effectively enhance the functionality of PPy-containing coatings.…”
Section: Introductionmentioning
confidence: 99%
“… Ku and Park (2010) introduced PDA coatings for potential vascular tissue engineering applications ( Ku and Park, 2010 ). It has been shown that PDA offers simple, effective, and inexpensive alternative for bone tissue engineering compared to traditional surface modification and tissue regeneration ( Huang S. et al, 2016 ; Lee et al, 2017 ; Zhou et al, 2019 ). Madhurakkat Perikamana et al (2015) have discussed in detail various techniques for versatile surface modification for tissue engineering.…”
Section: Applications Of Polydopamine Nanocoatingsmentioning
confidence: 99%